(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2011)
FEITOS DA PRESIDÊNCIA SLAT 0031404-98.2010.4.03.0000 Desembargador Federal Roberto Haddad 105/273 SLAT 0036039-25.2010.4.03.0000 Desembargador Federal Roberto Haddad 105/278 SLAT 0037604-24.2010.4.03.0000 Desembargador Federal Roberto Haddad 105/285 SLAT 0038002-68.2010.4.03.0000 Desembargador Federal Roberto Haddad 105/292 FEITOS DA VICE-PRESIDÊNCIA RE AMS 0014700-29.1999.4.03.6100 Desembargador Federal André Nabarrete 105/298 REsp ACr 0006995-23.2002.4.03.6181 Desembargador Federal André Nabarrete 105/303 CauInom 0036017-64.2010.4.03.0000 Desembargador Federal André Nabarrete 105/314 CauInom 0036790-12.2010.4.03.0000 Desembargador Federal André Nabarrete 105/320 DECISÕES MONOCRÁTICAS AC 0060287-74.1999.4.03.6100 Desembargadora Federal Vesna Kolmar 105/337 MS 0021228-60.2010.4.03.0000 Desembargadora Federal Suzana Camargo 105/342 CC 0022537-19.2010.4.03.0000 Desembargador Federal José Lunardelli 105/349 AI 0034992-16.2010.4.03.0000 Desembargador Federal Márcio Moraes 105/355 AI 0035407-96.2010.4.03.0000 Juiz Federal Carlos Francisco 105/359 JURISPRUDÊNCIA AGRAVO Ag REOMS 0025464-74.1999.4.03.6100 Desembargador Federal Luiz Stefanini 105/364 Ag ApelReex 0031710-87.2006.4.03.6182 Desembargadora Federal Cecília Marcondes 105/369 Ag AMS 0001408-41.2009.4.03.6127 Desembargador Federal Antonio Cedenho 105/379 AGRAVO DE INSTRUMENTO AI 0033003-19.2003.4.03.0000 Desembargador Federal Newton De Lucca 105/387 AI 0032690-19.2007.4.03.0000 Desembargadora Federal Salette Nascimento 105/393 AI 0038686-27.2009.4.03.0000 Desembargador Federal Fábio Prieto 105/400 AI 0045011-18.2009.4.03.0000 Juiz Federal Batista Gonçalves 105/412 AI 0011288-71.2010.4.03.0000 Desembargadora Federal Regina Costa 105/417 AI 0022991-96.2010.4.03.0000 Desembargadora Federal Marianina Galante 105/421 AGRAVO REGIMENTAL AgRg Apel Reex 0032990-83.2009.4.03.9999 Desembargador Federal Walter do Amaral 105/426 AgRg RpCr 0041521-85.2009.4.03.0000 Desembargadora Federal Therezinha Cazerta 105/434 APELAÇÃO CÍVEL AC 0274225-85.1981.4.03.6100 Desembargador Federal Lazarano Neto 105/466 ApelReex 0639621-28.1984.4.03.6100 Desembargadora Federal Marli Ferreira 105/471 AC 0003701-90.1994.4.03.6100 Juíza Federal Eliana Marcelo 105/478 Apel Reex 0035312-27.1995.4.03.6100 Desembargadora Federal Lucia Ursaia 105/501 AC 0034554-54.1996.4.03.9999 Juiz Federal Marcelo Aguiar 105/511 AC 0061143-49.1997.4.03.9999 Juiz Federal Heraldo Vitta 105/522 AC 0901107-43.1997.4.03.6110 Juiz Federal Souza Ribeiro 105/536 AC 1008074-75.1998.4.03.6111 Desembargadora Federal Cecilia Mello 105/559 AC 0001261-48.1999.4.03.6100 Juiz Federal Roberto Jeuken 105/597 AMS 0058458-58.1999.4.03.6100 Juíza Federal Silvia Rocha 105/607 AC 0001538-70.2000.4.03.9999 Juiz Federal Fernando Gonçalves 105/613 AC 0003646-17.2000.4.03.6105 Juiz Federal Nelson Porfírio 105/618 AC 0004581-60.2000.4.03.6104 Juíza Federal Giselle França 105/621 ApelReex 0000080-81.2001.4.03.6119 Juiz Federal Wilson Zauhy 105/632 AMS 0027374-68.2001.4.03.6100 Juiz Federal Rubens Calixto 105/637 AC 0000113-52.2002.4.03.6114 Juiz Federal Santoro Facchini 105/643 AMS 0001055-86.2003.4.03.6102 Desembargadora Federal Alda Basto 105/648 AMS 0003485-05.2003.4.03.6104 Juiz Federal Silva Neto 105/657 AC 0004202-14.2003.4.03.6105 Juiz Federal Paulo Conrado 105/667 AC 0004472-02.2003.4.03.6117 Desembargador Federal Johonsom di Salvo 105/672 AMS 0012369-35.2003.4.03.6100 Juiz Federal Valdeci dos Santos 105/679 AC 0017207-21.2003.4.03.6100 Juiz Federal Leonel Ferreira 105/688 AC 0022749-20.2003.4.03.6100 Juiz Federal Alessandro Diaferia 105/695 AMS 0018222-88.2004.4.03.6100 Desembargadora Federal Consuelo Yoshida 105/707 ApelReex 0000156-34.2006.4.03.6183 Juíza Federal Márcia Hoffmann 105/717 AMS 0000917-11.2006.4.03.6104 Juiz Federal Paulo Sarno 105/723 AC 0004515-70.2006.4.03.6104 Desembargadora Federal Marisa Santos 105/728 AMS 0006356-15.2006.4.03.6100 Desembargador Federal Mairan Maia 105/732 Apel Reex 0014738-45.2007.4.03.6105 Juíza Federal Marisa Cucio 105/746 AC 0001306-74.2008.4.03.6120 Desembargadora Federal Eva Regina 105/762 AMS 0002382-72.2008.4.03.6108 Desembargadora Federal Diva Malerbi 105/791 AC 0007092-68.2009.4.03.9999 Desembargador Federal Sérgio Nascimento 105/810 APELAÇÃO CRIMINAL ACr 0008247-92.2002.4.03.6106 Desembargador Federal Nelton dos Santos 105/816 ACr 0010054-10.2003.4.03.6108 Desembargador Federal Henrique Herkenhoff 105/822 ACr 0001580-56.2004.4.03.6127 Desembargadora Federal Ramza Tartuce 105/838 ACr 0002770-50.2005.4.03.6117 Juíza Federal Raquel Perrini 105/867 ACr 0002736-35.2010.4.03.6106 Desembargador Federal Cotrim Guimarães 105/872 CONFLITO DE COMPETÊNCIA CC 0010859-41.2009.4.03.0000 Desembargador Federal André Nekatschalow 105/894 CONFLITO DE JURISDIÇÃO CJ 0026388-03.2009.4.03.0000 Desembargador Federal Peixoto Junior 105/905 EMBARGOS DE DECLARAÇÃO EDcl AC 0063271-08.1998.4.03.9999 Desembargadora Federal Leide Polo 105/913 EDcl AC 0061852-79.2000.4.03.9999 Desembargadora Federal Vera Jucovsky 105/919 EDcl AC 0000263-52.2001.4.03.9999 Desembargador Federal Nelson Bernardes 105/923 EDcl AI 0006167-43.2002.4.03.0000 Juiz Federal Roberto Lemos 105/926 “HABEAS CORPUS” HC 0020323-55.2010.4.03.0000 Desembargador Federal Nery Júnior 105/933 HC 0029450-17.2010.4.03.0000 Desembargador Federal Carlos Muta 105/936 REEXAME NECESSÁRIO CÍVEL REO 0075153-98.1997.4.03.9999 Juiz Federal César Sabbag 105/955 REOMS 0035688-67.2006.4.03.9999 Juiz Federal João Consolim 105/957